1970
DOI: 10.1111/j.1365-2621.1970.tb12359.x
|View full text |Cite
|
Sign up to set email alerts
|

Pasteurization of Pacific Oysters by Radiation: Post‐Mortem Changes in Nucleotides During Storage at 0‐2°C

Abstract: SUMMARY: The concentration of nucleotides was lower in the adductor muscle of the oyster (1.64 μmoles/g) than in the remaining dark tissues of the oyster (2.75 μmoles/g). The concentration was less in the whole oyster meats (2.87 μmoles/g) than is usually found in fish muscle, or other marine invertebrates. In addition to the adenine nucleotides and inosine monophosphate, uridine triphosphate, guanosine triphosphate, guanosine diphosphate, guanosine monophosphate and guanosine diphosphate‐mannose were found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Liu et al (1992) reported that irradiation at a dose of 1 kGy was shown to have little effect on the concentrations of nucleotide catabolites in silver carp and tilapia. However, it was reported that the nucleotide breakdown in oysters stored at 0-2°C was not changed by 20 kGy radiation doses (Guardia & Dollar, 1970). Hx concentrations in hybrid striped bass irradiated at different radiation doses (2.0, 3.0 kGy and 20 kGy) were similar to nonirradiated samples (Karahadian et al, 1997).…”
Section: Nucleotide Degradation Productsmentioning
confidence: 92%
“…Liu et al (1992) reported that irradiation at a dose of 1 kGy was shown to have little effect on the concentrations of nucleotide catabolites in silver carp and tilapia. However, it was reported that the nucleotide breakdown in oysters stored at 0-2°C was not changed by 20 kGy radiation doses (Guardia & Dollar, 1970). Hx concentrations in hybrid striped bass irradiated at different radiation doses (2.0, 3.0 kGy and 20 kGy) were similar to nonirradiated samples (Karahadian et al, 1997).…”
Section: Nucleotide Degradation Productsmentioning
confidence: 92%